Geochemistry of a crude oil from a shallow well in Bazian Area, Sulaimani, Kurdistan Region, NE Iraq - M.J.Mohialdeen, Ibrahim; Hamasalih, Luqman O.; Schwar, Lorenz (Sulaimani Journal for Pure and Applied Sciences, 2013)
A crude oil sample from a shallow well in Bazian area, Sulaimani Governorate, Kurdistan Region was analyzed physically and geochemically in terms of source and its biomarker content. Physical properties of the sample indicate that this crude oil have high boiling point which mean absence of light ends, and middle distillate (i.e. gases, naphtha, kerosene, diesel fuel, etc.) with specific gravity of 0.9572, and API equals to 16.32. Chemical analysis show the sulfur content about 1.7% as well as rich in Fe and Ca. GC/MS analysis indicate to absence of n-alkanes, this supported by the mass chromatogram of m/z85 which show no biomarkers related to n-alkanes in the sample. Only a small portion of tricyclic terpanes (Cheilanthanes) are present. Mass chromatogram of m/z 217 shows some diasteranes, while other steranes are totally absent. No clear aromatic compounds were found in the studied sample. Severe biodegradation was indicated by the shape of chromatogram, absence of n-alkanes, partial degradation of steranes, remaining of diasteranes. The process of water washing may be accompanied with biodegradation as the aromatic components are removed. The presence of tricyclic terpanes usually related to non-terrestrial source material, which possibly the Kolosh Formation and/or older rock units are the source of this heavy oil.
Keywords: Biodegradation; Biomarkers; Kurdistan Region; Kolosh Formation